Comparison of laparoscopic partial nephrectomy performed with AirSeal® system vs. standard insufflator: results from a referral center - Forte, Flavio; Tripodi, Domenico; Pironi, Daniele; Corongiu, Emanuele; Gagliardi, Federica; Frisenda, Marco; Gallo, Gaetano; Quarantiello, Antonia; Di Lorenzo, Giuseppe; Cavaleri, Yuri; Salciccia, Stefano; Lori, Eleonora; et al. (Frontiers in Surgery, 2023)
Objective: To compare perioperative and oncologic surgical outcomes during laparoscopic partial nephrectomy (LPN) performed by standard CO2 insufflation, with those from surgeries in which the AirSeal® intelligent insufflation system was used for renal tumors. Methods: A total of 27 patients with renal tumor were identified, 14 who underwent LPN with AirSeal® (Group A) and 13 LPN with standard insufflator (Group B), respectively. Demographic baseline characteristics were similar in the two groups. The size of the tumor was largest in group B (29.64 versus 32.1 mm). The mean operative time was shorter in the AirSeal® group (group A: mean 109.0 minutes, median 107.5 minutes, IQR 85; group B: mean 121.0 minutes, median 120.0 minutes, IQR 50.0). Results: Positive margin rates were absent in the two groups. Estimated blood loss presented a difference in the perioperative period (group A, mean 1.5 g/dL, median 1.45 g/dL, group B mean 2.15 g/dL, median 2.2 g/dl). Time to ischemia was found to be shorter in group A with a median of 18 minutes, compared to a median of 20 minutes in group B. No subcutaneous emphysema, pneumothorax and pneumomediastinum cases occurred in either group. A postoperative complication developed in one patient requiring super-selective embolization. Conclusion: In selected patients, our preliminary surgical experience has shown that the LPN procedure performed with the aid of the Airseal® intelligent insufflation system can be used to treat even medium/high complexity kidney lesions, with a reduction in operating times, lower rates of complications and perioperative blood loss.